2016
DOI: 10.1016/j.nicl.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

A ‘complex’ of brain metabolites distinguish altered chemistry in the cingulate cortex of episodic migraine patients

Abstract: Despite the prevalence of migraine, the pathophysiology of the disease remains unclear. Current understanding of migraine has alluded to the possibility of a hyperexcitable brain. The aim of the current study is to investigate human brain metabolite differences in the anterior cingulate cortex (ACC) during the interictal phase in migraine patients. We hypothesized that there may be differences in levels of excitatory neurotransmitters and/or their derivatives in the migraine cohort in support of the theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 81 publications
(91 reference statements)
2
17
0
Order By: Relevance
“…18 A molecular-level study revealed altered N-acetyl aspartate/creatinine in the ACC in migraine patients. 19 Taken together, these findings indicate that the ACC plays an important role in the pathogenesis of migraine, especially CM. The ACC is involved in chronic neuropathic pain and its associated anxiety.…”
Section: Introductionmentioning
confidence: 79%
“…18 A molecular-level study revealed altered N-acetyl aspartate/creatinine in the ACC in migraine patients. 19 Taken together, these findings indicate that the ACC plays an important role in the pathogenesis of migraine, especially CM. The ACC is involved in chronic neuropathic pain and its associated anxiety.…”
Section: Introductionmentioning
confidence: 79%
“…A single case study is not convincing to argue that this is typical of pediatric migraineurs, although several studies of migraine in adults have shown decreased NAA in various regions of the brain; [99][100][101][102][103] one study observed an increase in NAA in the pons in episodic migraineurs, 104 and many studies have not observed any differences in NAA levels in various regions of the brain. 84,85,97,[105][106][107][108][109][110][111][112][113][114] Location, in addition to type of migraine, and migraine severity may also confound results and explain some of these discrepancies. A recent review argued that, instead of indicating neuronal loss, these reductions in NAA could indicate mitochondrial dysfunction, as mitochondria are proposed to synthesize NAA.…”
Section: Metabolitesmentioning
confidence: 99%
“…Magnetic resonance spectroscopy studies demonstrated neurochemical differences mainly in the cingulate and occipital cortices in patients with migraine. 6,7 Functional MRI studies found altered activation in regions related to pain processing, and the activity of resting-state networks was also shown to be altered in migraine. 8 Several diffusion tensor imaging (DTI) studies found microstructural abnormalities of the white matter in patients with migraine in pathways related to pain sensation 9 and visual processing.…”
mentioning
confidence: 99%